Carceral recovery: prisons, drug markets, and the new pharmaceutical self - Khan, Sanaullah (Lexington Books, 2024)
"Carceral Recovery is a medical anthropologist's account of demoralizing disciplinary and punitive approaches that continue to shape people's experience of recovery in an American city and makes a case for dis-entangling punitive approaches from the experience of substance use"--